Konsep Fair Price dalam Ekonomi Islam: Perspektif Historis, Filosofis dan Implementasi Sistem Perdagangan Modern - Linda Sari, Mailatun; Fadllan, Fadllan; Ningsih, Sri Wahyuni; Dwi Aprianto, Mohammad Andri (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The concept of fair price in Islamic economics is a fundamental aspect that emphasizes the balance between economic profit and moral principles. In Islamic economics, fair prices are not only determined by market mechanisms, but also consider ethical values, social justice, and common welfare. This article uses the literature review method (Library Research) to analyze the concept of fair prices in various Islamic perspectives. The results of the study show that: 1) Historically, Fair Price has been applied since the time of the Prophet PBUH by rejecting the practice of monopoly, hoarding, and fraud, and emphasizing fairness in transactions. 2) Philosophically, this concept is rooted in the principles of maslahah (benefit) and adl (justice), which ensures that the price of an item reflects its fair value without harming one party. 3) In modern practice, this concept is implemented in sharia-based price regulations, halal trading systems, and Islamic economic policies that emphasize transparency and social welfare. The results of this study show that Fair Prices in Islamic economics remain relevant in building a fairer and more sustainable trading system